Personal Characteristics as Determinants Towards Intention For Financial Reporting Fraud - AWANG, YUNITA; RAHMAN, ABDUL RAHIM ABDUL; ISMAIL, SUHAIZA; RASHID, NORFADZILAH (The journal of contemporary issues in business and government, 2021)
Purpose –This study attempts to examine the level of intention for financial reporting fraud; and, to determine whether personal characteristics act as determinants of such intention among Muslim participants in the financial reporting process at Malaysian banking institutions. Design/methodology/approach – Using questionnaire, the data was obtained based on non- probability purposive sampling from 121 Muslim accounting practitioners who are the participants in the financial reporting process of Malaysian banking institutions. The data is analysed using SPSS. Findings – The findings indicate a low intention for financial reporting fraud. Only bank type and working experience in the present banking institutions are significant in determining the intention for financial reporting fraud. Research limitations/implications – The study adds to the scant literature investigating personal characteristics influencing intentions for financial reporting fraud in the banking sector. The findings give insights to the banks’ stakeholders on the personal characteristics that may determine the intention for financial reporting fraud among the actual participants in the financial reporting process within Malaysian banking institutions. However, the use of scenario in this study may lead to the issue of social desirability bias, while the use of purposive sampling technique may limits the generalizability of its results. Originality/value - This study examined personal characteristics of the actual participants or preparers in the financial reporting process within Malaysian banking institutions as determinants towards intention for financial reporting fraud. This study enhances the value of financial reports prepared and the trustworthiness of Muslim preparers in performing their professional duties to fulfil the financial reporting process.